If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -4 * 0 = 24 Multiply -4 * 0 -6x + 0 = 24 Anything times zero is zero. -6x + 0 = 24 Reorder the terms: 0 + -6x = 24 Remove the zero: -6x = 24 Solving -6x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-6'. x = -4 Simplifying x = -4
| 20x^3+58x^2+42x=0 | | 36x^2-81= | | -8x+83=-85+16x | | -185-35x=0 | | 9y/11=-9 | | 14+3x=2+5x+5 | | 7x+8x=45-90 | | 6x+3=-45-2x | | 5(3x-2)=35+45 | | 2(h-1)=3(h+1) | | (2x-7/12)+x=(2x+7/2)+3 | | 5x^2+7x+95=0 | | .3333(5x-8)=3 | | y=2x+22/5 | | onethird(5x-8)=3 | | 5y=2x+22 | | -4x+13-2x=3x-11 | | 2x-5/3+5=8 | | -9m+m^2=0 | | (11b+9)(2b-3)=0 | | 2(x-7)-1=5(3x+1) | | 3x/5+2x=0 | | (t/8+5)=7 | | x=3x+7(x-8) | | -8=4(9-2)+4 | | 3x-x/8=30 | | 7-3r=r-4(5-2/5r) | | 6=4/5+5 | | -13=h-1 | | 0-4x+7=11 | | g(t)=3t-3 | | 2.8=6/4 |